Efeitos econômicos da COVID-19 sobre o faturamento de empresas do segmento de restaurantes e lanchonetes na Paraíba - Bermeo, Caren Gabriela Castillo (2021)
In the current context of the pandemic generated by Covid-19 that directly affects people’s health and the countries’ economies, governments have had the need to implement various policies through decrees to promote distance and social isolation, in view of this, the establishments considered non-essential among them, restaurants and snack bars, felt the need to close or change the way they operated, at the same time, individuals experienced a rapid change in daily routine and in the way of consumption, which boosted sales through delivery platforms that in the global market were already growing in recent years. However, studies of delivery platforms focus mainly on consumer preferences or type of company, and empirical studies, such as assessing the impact of social isolation due to the COVID-19 pandemic in companies with sales by delivery, are still scarce. In view of this scenario, the objective of this work is to evaluate the possible economic effects of the pandemic in the food sector using the Differences in Differences (DD) model from the invoicing of establishments, and considering automation through digital services for orders and deliveries. delivery in the food sector in Paraíba-Brazil. The results of the study show that the technology seen as digitization adapted by establishments at the time of the pandemic can help significantly reduce the negative effects on losses in gross revenue. Therefore, it is demonstrated that the use of online food ordering and delivery service platforms can assist in the survival of establishments and the preservation of work in the food sector.